2017
DOI: 10.1186/s12916-017-0909-2
|View full text |Cite
|
Sign up to set email alerts
|

What works for whom in the management of diabetes in people living with dementia: a realist review

Abstract: BackgroundDementia and diabetes mellitus are common long-term conditions and co-exist in a large number of older people. People living with dementia (PLWD) may be less able to manage their diabetes, putting them at increased risk of complications such as hypoglycaemia. The aim of this review was to identify key mechanisms within different interventions that are likely to improve diabetes outcomes in PLWD.MethodsThis is a realist review involving scoping of the literature and stakeholder interviews to develop t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 119 publications
0
22
0
Order By: Relevance
“…People living with dementia, particularly those in advanced stages, are often excluded from trials 27 28. As a result, existing evidence for the pharmacological management of chronic conditions (eg, diabetes) does not fully reflect the needs of people with dementia, nor does it provide conclusive evidence that it improves health outcomes or quality of life 44 51 52. A 2018 systematic review on management of chronic conditions in people with dementia identified only six studies, covering depression, osteoporosis, diabetes and cardiovascular disease 44.…”
Section: Discussionmentioning
confidence: 99%
“…People living with dementia, particularly those in advanced stages, are often excluded from trials 27 28. As a result, existing evidence for the pharmacological management of chronic conditions (eg, diabetes) does not fully reflect the needs of people with dementia, nor does it provide conclusive evidence that it improves health outcomes or quality of life 44 51 52. A 2018 systematic review on management of chronic conditions in people with dementia identified only six studies, covering depression, osteoporosis, diabetes and cardiovascular disease 44.…”
Section: Discussionmentioning
confidence: 99%
“…Realist reviews have been used to understand a variety of complex health interventions with multimorbid populations. 31,32 The methods draw on a realist philosophy, taking a "generative" view of how interventions work (including contextual factors), as opposed to a more positivist "successionist" view. 33 Realist reviews are explanatory, seeking to unpick the important mechanisms underlying sets of interventions.…”
Section: Methods Designmentioning
confidence: 99%
“…This is unsurprising, as diabetes is largely a self-managed disease that necessitates high-level cognitive capabilities for patients to properly adhere to medication and lifestyle regimens. However, memory loss, impaired problem-solving, and other ADRD symptoms make diabetes management extremely difficult for people living with ADRD and their family caregivers [ 14 , 60 ]. Previous recommendations and studies have suggested that for people with cognitive impairment, diabetes care should be individualized and patient-centered [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, memory loss, impaired problem-solving, and other ADRD symptoms make diabetes management extremely difficult for people living with ADRD and their family caregivers [ 14 , 60 ]. Previous recommendations and studies have suggested that for people with cognitive impairment, diabetes care should be individualized and patient-centered [ 60 ]. The glycemic target (eg, hemoglobin A 1c , fasting glucose, and postprandial glucose) should also be relaxed [ 14 ].…”
Section: Discussionmentioning
confidence: 99%